ANALISIS STRUCTURAL EQUATION MODELLING DAN TERAPANNYA (Studi Kasus: Pengaruh Kualitas dan Relationship Marketing Terhadap Kepuasan, Kepercayaan dan Loyalitas Mahasiswa Terhadap Perpustakaan UIN Alauddin Makassar) - -, Irwan; Idris, Aditya (Teknosains, 2014)
Structural Equation Modeling ( SEM ) is a multivariate analysis were used to analyze the relationship between variables in a complex manner. University libraries in higher education has a vital role. University libraries can be said to be at the heart of higher education, as it became a major contributory factor for the implementation of Tri Dharma Perguruan Tinggi. Quality of service at the library is very important to the success of service is realized as a library service. This study aims to determine the SEM parameter estimation using Maximum Likelihood as well as to analyze the effect of variable quality and relationship marketing in relation to satisfaction, trust and loyalty student UIN Alauddin Makassar students. This study was conducted by questionnaire, the data obtained by distributing questionnaires to 116 respondents. The population in this study was student UIN Alauddin Makassar. The sampling method used was Accidental Sample.Quality of service at UIN Alauddin Makassar Library does not have a significant effect on student satisfaction and confidence, while relationship marketing is done by the Library of UIN Alauddin Makassar in fact have a significant effect on student satisfaction and confidence UIN. From the calculation of the index Loyalty student UIN UIN Alauddin Makassar Library by 86%. For the lowest level of this calculation is that the satisfaction index of 65%. And for the student confidence index value of UIN Alauddin Makassar Library by 70%. The third variable is measured by the quality of services and relationship marketing carried out in the UIN Alauddin Makassar Library.Keywords: SEM, Maximum Likelihood, Service Quality, Relationship Marketing, Satisfaction, Confidence, Student Loyalty.